EFEKTIVITAS PENGGUNAAN MEDIA CETAK LEAFLET DAN FOLDER TERHADAP TINGKAT PENGETAHUAN PETANI SAYURAN DALAM PEMBUATAN PUPUK KOMPOS DI DESA WONUA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Sukmawati Abdullah (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to analyze the effectiveness of using printed media such as leaflets and folders in increasing the knowledge of vegetable farmers in compost production in Wonua Village, Konda District, South Konawe Regency. The problem of low farmer knowledge about proper composting techniques has resulted in the suboptimal utilization of organic waste as a source of fertilizer raw materials. Printed media such as leaflets and folders were chosen because they are easy to understand, inexpensive, and can be studied independently. The sample size has taken by census model and data obtained by direct interview. Variables observed to print of media consist of leaflet and folders and knowledge scores of respondents by measuring the increase of knowledge on the material presented in the media leaflets and folders in the manufacture of compost on vegetable crops. Obtained data is tabulated, made to be percentage and then will be analyzed by descriptive qualitative. The results of this research show that effectiveness of increasing farmers' knowledge of vegetables in the composting through print leaflets quite effectively with a value of 61.19 percent while the percentage for the use of folders in the print media is less effective with the percentage of 48.03 percent in the farmer respondents.